Early Detection of Central Nervous System Abnormalities by Neurosonography in Critically Ill Neonates - Amar Taksande; Rupesh Rao (Mashhad University of Medical Sciences, 2021)
Background: Neurosonography has been widely used for screening and early detection of Central Nervous System (CNS) defects, such as intraventricular hemorrhage, hydrocephalus, cerebral edema, or any structural anomalies in the neonatal brain in the neonatal intensive care unit (NICU) of a tertiary level hospital. The present study aimed to assess the detection of CNS abnormalities by neurosonography in critically ill neonates.Methods: This prospective cross-sectional study at the Neonatology Unit of the Paediatric Department of Acharya Vinoba Bhave Rural Hospital (AVBRH). A neonate was described as "critically ill" based on detailed maternal history and clinical examination. These neonates were subjected to neurosonography according to the inclusion and exclusion criteria in accordance with the noted protocols and various anomalies. Gestational age, birth weight, clinical examination, investigation, neurosonography finding, and outcomes were evaluated.Results: Neurosonography was performed in 105 critically ill neonates, out of whom 21 cases had abnormal neurosonography findings. Abnormal neurosonography was not significantly correlated with birth weight and gestational age of high-risk neonates (P=0.538 &P=0.130). The most frequent clinical manifestation was respiratory distress syndrome, followed by a neonatal seizure. The mean scores of heart rate, respiratory rate, systolic blood pressure, diastolic blood pressure, and oxygen saturation were obtained at 140±19.81, 54.08±13.07, 90.96±8.66, 54.13±8.39, and 94.39±6.93, respectively.Conclusion: Neurosonography is a useful tool in NICU. It is an acceptable and reliable modality to screen critically ill neonates, assisting the early detection and management of these ill neonates.